2017
DOI: 10.1111/psyp.13042
|View full text |Cite
|
Sign up to set email alerts
|

EEG frequency PCA in EEG‐ERP dynamics

Abstract: Principal components analysis (PCA) has long been used to decompose the ERP into components, and these mathematical entities are increasingly accepted as meaningful and useful representatives of the electrophysiological components constituting the ERP. A similar expansion appears to be beginning in regard to decomposition of the EEG amplitude spectrum into frequency components via frequency PCA. However, to date, there has been no exploration of the brain's dynamic EEG-ERP linkages using PCA decomposition to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 39 publications
(51 reference statements)
5
35
1
Order By: Relevance
“…Nonsignificant relationships between no‐go error rates and ERP components were expected here. For resting state intrinsic EEG, similar f‐PCA outcomes as those identified by Barry and De Blasio () were anticipated. These consisted of a frontocentral delta component, a second factor overlapping the delta/theta band ranges, three posterior alphas, and two parietal‐midline beta components.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Nonsignificant relationships between no‐go error rates and ERP components were expected here. For resting state intrinsic EEG, similar f‐PCA outcomes as those identified by Barry and De Blasio () were anticipated. These consisted of a frontocentral delta component, a second factor overlapping the delta/theta band ranges, three posterior alphas, and two parietal‐midline beta components.…”
Section: Introductionsupporting
confidence: 77%
“…Although this finding is comparable to prior studies indicating a direct relationship between P3b amplitude and broad-range (8-13 Hz) alpha (De Blasio & Barry, 2013b;De Blasio et al, 2013) and also subdivided alpha power (Intriligator & Polich, 1995;Polich, 1997), it is the first report involving a resting state f-PCA component. Barry and De Blasio (2018) did not examine resting state EEG components in relation to ERPs, focusing only on the prestimulus EEG components. In their study, distinct P3b effects were found: Prestimulus alpha-1 and alpha-3 were inversely related to P3b amplitude, while alpha-2 directly predicted P3b enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to resting theta oscillations, the alpha rhythm dominates the resting EEG, with most individuals showing a distinct alpha peak at about 10 Hz having a robust posterior topography (Aurlien et al, 2004;Chiang, Rennie, Robinson, van Albada, & Kerr, 2011). Moreover, the alpha rhythm is prominent (e.g., visible in raw EEG traces) and reliably quantified by different research groups using different methodologies (e.g., Barry & De Blasio, 2018;Labounek et al, 2018;Schmidt et al, 2017;Shackman et al, 2010;Sockeel, Schwartz, Pélégrini-issac, & Benali, 2016;Tenke et al, 2017). Importantly, greater posterior alpha oscillations at rest predicted a favorable clinical outcome for individuals diagnosed with MDD (Baskaran et al, 2017;Bruder et al, 2008;Jaworska, de la Salle, Ibrahim, Blier, & Knott, 2019;Kandilarova et al, 2017;Knott et al, 1996;Tenke et al, 2011;Ulrich, Renfordt, Zeller, & Frick, 1984;Ulrich, Renfordt, & Frick, 1986; although see Arns et al, 2016, andKnott, Mahoney, Kennedy, &Evans, 2000, for unsuccessful attempts to replicate these findings).…”
Section: Research Findings On Posterior Alphaband Activity As a Canmentioning
confidence: 99%
“…Since transforming from time domain to frequency domain requires EEG data lasting for some duration being processed, it means some unusual variance is discarded at the same time. Based on these global and stable features more sophisticated biomarkers can be achieved [16].…”
Section: Controller Networkmentioning
confidence: 99%